PENGARUH KEPEMIMPINAN DAN ABILITY TERHADAP KINERJA KARYAWAN PADA PT. TIKI CABANG PEKANBARU - Ningsih, Dewita Suryati; Fitri, Kurniawaty; ', Suparman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study was 1) to analyze the influence of leadership and ability simultaneously to the performance of employees at PT. TIKI Branch of Pekanbaru. 2) To analyze the effect of leadership on employee performance partially PT. TIKI Branch of Pekanbaru. 3) To analyze the effect of the partial ability of the performance of employees at PT. TIKI Branch of Pekanbaru. Based on the conclusions that have been described above, the authors are able to present some suggestions: 1) It is recommended PT.TIKI management Pekanbaru branch leadership to pay attention to factors and especially on indicators of the quality of work initiative dah. 2) Expected to employees in order to provide positive and constructive feedback. 3) It is recommended to management PT.TIKI Pekanbaru Branch to improve the performance of employees, in order to achieve a more optimal.Keywords: Leadership (X1), Ability (x2), Performance (Y)